Teachers' Counseling Competence in Parent-Teacher Talks Modeling, Intervention, Behavior-Based Assessment - Gerich, Mara (Springer Fachmedien Wiesbaden : Imprint: Springer, 2016)
In her doctoral thesis, Mara Gerich makes an important contribution to research on the topic of teachers' counseling competence, particularly in the specific domain of parent-teacher talks with regard to the support of students' learning processes. The author gains insights that permit several implications for educational practice, particularly within the context of teacher preparation and continuing education. Parent counseling on the support of students' learning processes is emphasized as a central pedagogical task of teachers in international research on teacher professionalization and standards for teacher education. Contents Relevance and definition of teachers' counseling competence Development and empirical validation of a competence model Development and evaluation of a training program and a process-oriented feedback intervention for prospective teachers Development and validation of a behavior-based assessment tool Implications for educational research and practice Target Groups Lecturers and students of psychology, theory and methodology of education and educational science Teacher trainers, psychologists, teachers, family and child guide counselors About the Author Dr. Mara Gerich is a research assistant at the Institute of Psychology and the Center for Teacher Training at the Technical University of Darmstadt. Her scientific research focuses on the areas of counseling, teacher professionalization, competence research, and intervention research. .